Efek Hepatoprotektif Polifenol Coklat terhadap Gambaran Histopatologi Tikus Diabetes : Efek Hepatoprotektif Polifenol Coklat terhadap Gambaran Histopatologi Tikus Diabetes - Restuti, Arisanty Nur Setia; Yulianti, Adhiningsih; Ratri, Putri Rahayu (Universitas Airlangga, 2026)
Background: Diabetes mellitus is a growing global health concern, including in Indonesia, where its prevalence continues to rise. Persistent hyperglycemia and the resulting oxidative stress contribute to hepatic injury, including steatosis and hepatocellular necrosis. Cocoa contains polyphenolic compounds such as catechin and epicatechin, which are known to exert antioxidant effects and may help attenuate oxidative damage. Objective: This study evaluated the effect of chocolate drink administration on liver histopathological changes, particularly necrosis and steatosis, in a diabetic rat model. Methods: A post-test-only control group design was employed using 25 male Sprague Dawley rats divided into five groups: normal control (K–), diabetic control (K+), and three treatment groups receiving chocolate drinks at concentrations of 2%, 4%, and 6% (equivalent to 40, 80, and 120 mg/200 g body weight/day) for 14 days. Diabetes was induced through a high-fat diet followed by streptozotocin injection. Liver tissues were stained with hematoxylin–eosin. Necrosis was assessed using the Manja Roenigk scoring system, while steatosis was evaluated based on percentage criteria. Results: A significant difference in hepatocyte necrosis was observed among groups (p=0.016), with treated groups showing lower necrosis compared to the diabetic control. In contrast, steatosis did not differ significantly between groups (p=0.515). Conclusion: Chocolate drink administration was associated with reduced hepatocellular necrosis in diabetic rats, suggesting a protective effect likely mediated by antioxidant mechanisms. However, no significant improvement in steatosis was observed within the short intervention period. Longer treatment duration or alternative dosing strategies may be required to influence lipid accumulation in the liver.